Study on Water Balance in Poteran – A Small Island in East Java, Indonesia. (2015) - Tatas,; Budipriyanto, Agung; Khoiri, Mohamad; Lestari, Wien; Rahman, Askur
Abstract: Study on water balance in a small island is essential to be conducted. A small island normally has small catchment areas so that most of the surface rain water flows quickly into the sea. Consequently, it causes limited recharge of rainwater into groundwater. When the usage of groundwater is high, the water demand-supply could be unbalance. It will certainly cause problems, such as seawater intrusion or water crisis. There are numbers of small islands in Indonesia; in most of these islands, the water balance has not been studied yet. This paper discusses water balance in Poteran- a small island in East Java, Indonesia. The island area is only 49.8 km 2 with population of nearly 50, 000 people. The land use in the island is dominated by agricultural areas. In this study, some investigations are conducted including survey of land-surface area, collecting meteorology and climatology data. Thornthwaite approach is used for computing evapotranspiration in water balanced calculation. The results show soil texture dominant is clay loam, with a land use is corn farming (root depth is 0.8 meters), field capacity is estimated 0.25 and permanent wilting point values is 0.12. Precipitation is 1790 mm, the potential evapotranspiration is 2047 mm, water surplus is 300 mm and water deficit is 557 mm a year. The results suggest that the Poteran Island has limited recharge water that could be lead to a water crisis in the future.